When, where and whom: assessing wildlife attacks on people in Chitwan National Park, Nepal. Issue 2 (10th May 2016) - Silwal, Thakur; Kolejka, Jaromir; Bhatta, Bharat P.; Rayamajhi, Santosh; Sharma, Ram P.; Poudel, Buddi S.
Abstract: Wildlife attacks on people in and around protected areas have become one of the main challenges for wildlife management authorities. We assessed all correlates of wildlife attacks during 2003–2013 in the vicinity of Chitwan National Park, Nepal. We used data from various sources (discussion with stakeholders, field observations, questionnaire surveys). Wildlife attacks were significantly correlated to factors such as site, season and time, activity, gender and awareness. Moreover, 89% of recorded attacks occurred outside the Park. The number of attacks fluctuated widely and patterns of attacks were significantly uneven across seasons and months. Of the 87% of attacks that occurred during the day, 63% occurred in the morning. Most victims were male and c. 45% of attacks occurred when people were collecting forest resources or working on croplands. Attacks were carried out predominantly by rhinoceros Rhinoceros unicornis (38%), tigers Panthera tigris (21%), sloth bears Melursus ursinus (18%), elephants Elephas maximus (9%) and wild boar Sus scrofa (8%). The people attacked lived close to the Park, depended on farming for their livelihoods, and had little knowledge of animal behaviour. Attacks can be mitigated through proper management of habitats inside the Park and raising awareness of wildlife behaviour among local people. We recommend establishing a participatory emergency rescue team to deal with problematic animals in high-risk areas.